How Not to Kill Your Houseplant Survival Tips for the Horticulturally Challenged - Peerless, Veronica (Dorling Kindersley Publishing, Incorporated New York, 2023)
"Yellowed leaves, drooping leaves, dried leaves even though you've watered it: what's going on? [This book] will explain--and fix--your houseplant woes. Learn to spot the danger signs and take the proper action to rescue your sick plant. Follow quick tips to understand what your plant does and doesn't like: how much light, water, food, heat, and humidity. Discover the perfect plant for your unique space and needs. Bathrooms, cold rooms, at a desk, on a windowsill, or in a gloomy corner or hot suntrap--there are plants for every location to create your own indoor oasis"--
112753
Keywords: House plants; Indoor gardening; Gardening / House Plants & Indoor